Exploring the Diversity of the Marine Environment for New Anti-cancer Compounds - Dayanidhi, Divya L.; Thomas, Beatrice C.; Osterberg, Joshua S.; Vuong, Mallissa; Vargas, Giselle; Kwartler, Sarah K.; Schmaltz, Emma; Dunphy-Daly, Meagan M.; Schultz, Thomas F.; Rittschof, Daniel; Eward, William C.; Roy, Christopher; et al. (Frontiers in Marine Science, 2021)
Marine ecosystems contain over 80% of the world’s biodiversity, and many of these organisms have evolved unique adaptations enabling survival in diverse and challenging environments. The biodiversity within the world’s oceans is a virtually untapped resource for the isolation and development of novel compounds, treatments, and solutions to combat human disease. In particular, while over half of our anti-cancer drugs are derived from natural sources, almost all of these are from terrestrial ecosystems. Yet, even from the limited analyses to date, a number of marine-derived anti-cancer compounds have been approved for clinical use, and several others are currently in clinical trials. Here, we review the current suite of marine-derived anti-cancer drugs, with a focus on how these compounds act upon the hallmarks of cancer. We highlight potential marine environments and species that could yield compounds with unique mechanisms. Continued exploration of marine environments, along with the characterization and screening of their inhabitants for unique bioactive chemicals, could prove fruitful in the hunt for novel anti-cancer therapies.